Penerapan Metode NNC (Nouthetic Nature Community) Yang Berdampak Pada Layanan Masyarakat - Ersada Siregar; Yanto Paulus (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The NNC (Nouthetic Nature Community) method is a new method that comes from combining Nouthetic which consists of the elements of Confrontation, Concern, and Change as well as the addition of Nature and Community elements, the author named the NNC method. The author created this new method based on the needs of members of a local church who were experiencing feelings of disappointment. One of the elements of NNC is Community which has an impact on services to the community, distribution of food to people in need, this community is named Dapoer Berkat. Dapoer Berkat community activities aim to ensure that each member experiences recovery through counseling, worship, prayer as well as the loving service of distributing food to the surrounding community. Dapoer Berkat chose this community service place in Ciangsana village, West Java because it is close to the community and in Ciangsana village there are quite a lot of elderly people who still work as janitors, rubbish collectors, and online motorbike taxis. The love of Christ drives Dapoer. Thanks to carrying out this ministry, love is a real action that can be felt by everyone.